Answer:
The graph with B(2,-3) i.e) y=
x goes through the point M(-10,15).
Step-by-step explanation:
Consider M(-10,15) and given that equation is y = kx.
Now, substitute M(-10,15) in the equation
⇒ 15 = k × -10
⇒ k =
= ![\frac{-3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B2%7D)
⇒ y =
x
Now, check with the given points B(2,-3) and B(
, -2)
1) B(2,-3)
y =
x
⇒(-3) =
× 2
⇒ -3 = -3 ⇒ LHS = RHS
⇒ B(2,-3) is the required point.
2) for b(
, -2)
LHS ≠ RHS.
So,The graph with B(2,-3) i.e) y=
x goes through the point M(-10,15).